The Hierarchical Structure of Selected Morphological and Motoric Variables in Ski Jumping - Jošt, Bojan (Human movement, 2010)
Purpose. The main purpose of the present research paper was to establish a hierarchical factor structure in a selected sample of morphological and motor variables of ski jumpers; such variables are base constituents of the potential performance model in ski jumping. Basic procedures. The subject sample was Slovene ski jumpers older than 15 years (n = 72), tested in May 2008. The research was done on a selection of 41 variables (12 basic morphological ones, seven from a special morphological index, 10 basic motoric ones and 12 special dynamic variables of take-off power). Main findings. Through factor analysis in the first phase, nine factors were excluded from the manifest variables of first orders: 1. Factor of velocity power (34.9% of variance); 2. Factor of longitudinal body dimensions (17.2% of variance); 3. Factor of morphological index of flight aerodynamics (12.2% of variance); 4. Factor of morphological index of take-off (7.3% of variance), 5. Factor of push-off explosive power (5.0% of variance), 6. Factor of informatic component of motorics (3.5% of variance); 7. Factor of specific morphological index of thigh dimensions (3.1% of variance), 8. Factor of transversal dimensions of body (2.4% of variance), 9. Factor of flexibility of hips (2.2% of variance). All nine factors of the first order explained 88% of variance of manifest variables. On the basis of configuration of nine factors of the first order in the second phase, four components were excluded from the second order with 62.7% of total variance. The first was component of specific take-off movement (22.9% of variance), followed by component of thigh dimension (14.5% of variance), then component of specific flight potential (13.0% of variance) and finally component of basic morphology (12.1% of variance). On the third level of factor analysis, two general factors of ski jumpers with 57.1% of total variance were found. The first was the general factor of specific movement of ski jumpers (29.8% of variance) and second the general factor of morphology (27.7% of variance). Conclusions. The research confirms the main hypothesis that hierarchical latent factor structures of manifest motor and morphological variables exist. The independent primary factors of the first order are crucial for understanding the latent dimensions of the potential performance model on the second and third level. This factor shows the structure between manifest dimensions more clearly and their relations are more understandable.